#GivingTuesday totals hit record high. Issue 341 (17th January 2018) - Unknown
Abstract : According to preliminary numbers, #GivingTuesday 2017 saw record‐breaking totals, with some $274 million raised during the one‐day event. That's a whopping 50 percent increase over the amount raised in 2016, and philanthropy experts believe the annual event will continue to grow in the years to come.